Satisfacción al usuario en la Unidad de Atención al Asegurado del Hospital General IESS Babahoyo - Sanchez Murillo, Ricardo Arturo (2019)
The present case study was carried out at the IESS Babahoyo general hospital, specifically in the insured care unit where the processes that are carried out have caused disagreements in the users due to the lack of professionalism of the officials. It is based on the research line Administrative management model, a qualitative type of investigation was used, the deductive method was applied, obtaining in a more reliable way information on the main stakeholders of the actions that deteriorate the image of the entity. The results obtained can be verified that the entity does not have duly trained and capable officials to provide an efficient and quality service meeting the expectations of the users